Pengaruh Sistem Informasi Akuntansi, Motivasi Kerja, dan Pengendalian Internal terhadap Kinerja Pegawai pada Kantor Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Karawang - Shafa Humaira; Fista Apriani Sujaya; Trisyanto, Ade (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The study conducted arose due to a decrease in employee performance in 2021 compared to 2020. Data collection using a questionnaire method with a population of 50 employees. Employee performance at the Karawang Regency Personnel and Human Resources Development Agency Office is the focus of the study carried out with the aim of understanding the role of information systems, work motivation, and internal control. Data were analyzed using SPSS descriptive techniques and multiple linear regression. Referring to the significance value of 0.005 <0.05, it means that the information system variable has a significant influence on the employee performance variable. The significance value of the employee work motivation relationship, namely 0.000, is still below the 0.05 figure so that the work motivation variable has a significant effect on employee performance. Meanwhile, the internal control variable has a significance value of 0.014, which is still below 0.05, so it can be interpreted that this variable affects employee performance. A significant value of 0.000 <0.05 indicates that accounting information systems, work motivation, and internal control affect employee performance. Based on these findings, improved accounting information systems, worker motivation, and the establishment of strong internal controls all contribute to better job performance. Things to do include implementing accounting information systems that help employee welfare and ensuring employees receive proper supervision